Congenital malformations in children of diabetic mothers in the province of Cienfuegos. 2016-2019 - Fanny Arbolay Sanabria; Lázaro Roberto Herrera Fragoso; Maylé Santos Solí; Gladys Bárbara Barberis Pérez; Walkiria Díaz Senra; María Soledad Vilches León (Medisur)
Foundation: the relationship between developmental alterations and poor glucose control in the pathogenesis of congenital malformations has been demonstrated. Objective: to identify congenital malformations in children of diabetic mothers. Methods: an observational, descriptive cross-sectional study was carried out on diabetic pregnant women whose children had malformations, in the province of Cienfuegos during the period 2016-2019. The variables maternal age, body mass index, type of diabetes, its treatment, type of malformation, ultrasonographic results of the three trimesters of pregnancy, alpha-fetoprotein study and amniocentesis were studied. Results: in the studied population the highest percentage of mothers presented gestational diabetes mellitus; Mothers between 20 and 35 years old predominated and a large number of them were overweight. The largest number of birth defects were diagnosed at the second trimester ultrasound (more than 90%). The treatments most used by pregnant women were diet and insulin. Major congenital malformations constituted the largest percentage and the most affected system was the cardiovascular system. Conclusions: diabetes mellitus and overweight continue to be risk factors for congenital malformations, so reducing them in women of reproductive age and planning pregnancy is important in the prevention of maternal diabetes and its impact on the product of conception.